The chemotherapy effect on embryonal rhabdomyosarcoma in a 2-year-old girl in a development country: A rare case (Indian Journal of Case Reports, 2021)
Rhabdomyosarcoma (RMS) is the third most common solid organ malignancy in children after Wilms tumor and neuroblastoma. It is a highly malignant tumor with local tissue invasion and lymphatic and hematogenous metastases. The main treatment for RMS is complete resection with a combination of chemotherapy and radiotherapy. Here, we present the case of a 2-year-old girl who came to the hospital with a complaint of noisy breathing (Stridor) for the past 2 weeks. Intraoral examination showed an oval mass at the base of the tongue that almost closed the airway, felt soft, and had a bump. A computed tomography scan of the neck was performed, and a solid lesion with clear irregular borders was found in the posterior lingua. Incisional biopsy was performed with histopathological results of embryonal RMS. Two weeks after the biopsy, chemotherapy was performed, and the evaluation after two chemotherapy sessions, the mass size was found to have decreased.